Animal models for assessing impact of C-section delivery on biological systems. (April 2022) - Cabré, Sílvia; Ratsika, Anna; Rea, Kieran; Stanton, Catherine; Cryan, John F.
Abstract: There has been a significant increase in Caesarean section (C-section) births worldwide over the past two decades and although it can be a life-saving procedure, the enduring effects on host physiology are now undergoing further scrutiny. Indeed, epidemiological data have linked C-section birth with multiple immune, metabolic and neuropsychiatric diseases. Birth by C-section is known to alter the colonisation of the neonatal gut microbiota (with C-section delivered infants lacking vaginal microbiota associated with passing along the birth canal), which in turn can impact the development and maintenance of many important biological systems. Appropriate animal models are key to disentangling the role of missing microbes in brain health and disease in C-section births. In this review of preclinical studies, we interrogate the effects of C-section birth on the development (and maintenance) of several biological systems and we discuss the involvement of the gut microbiome on C-section-related alterations. Highlights: C-section birth hampers vertical transmission of microbiota. C-section has been associated with a broad range of immune and metabolic diseases. Animal models of C-section can be used to study C-section mediated alterations. C-section birth modifies physiological and behavioural outputs. The microbiota-gut-brain axis mediates physiology and behaviour.